Skin Tear Prediction in the Elderly: A Cohort Study - Rayner, Robyn Louise (Curtin University, 2017)
Skin tears are common wounds found amongst older adults. A 6-month cohort study was conducted to investigate the reliability of non-invasive technologies to objectively quantify ageing skin properties, and to examine risk factors associated with 6-months incidents of skin tears, in an aged care population. Multivariable analysis developed a skin tear model with a receiver operator characteristic curve indicating the model provided very good discrimination for correctly classifying participants with and without skin tears.